The Effect of Viola Odorata L. Oil for Fever in Children: A Randomized Triple-blinded Placebo-controlled Clinical Trial - Tafazoli, Vahid; Shahriari, Mahdi; Heydari, Mojtaba; Nikbakht, Hosein A.; Zarshenaas, Mohammad M.; Nimrouzi, Majid (Current Drug Discovery Technologies, 2020)
Introduction: Finding non-systemic antipyretic option in cancer patients who simultaneously receive several other drugs seems be logical. This study was designed to evaluate complementary therapy with Viola odorata L. oil for fever control in febrile neutropenic children. Methods and Materials: In a randomized placebo controlled clinical trial, 41 febrile children were divided into two groups. Children in the active drug group received viola oil (20 drops) to be rubbed on the peripheral margin of the patient umbilicus. Primary outcome measure of the study was the mean axillary temperature in the 30, 60, and 240 minutes after the intervention. Results: The mean temperature reduced significantly in the viola group after 30 minutes of administration (p =0.005), while there was no significant change in the placebo group (p =1.00). The number of patients who received paracetamol as the rescue treatment was significantly lower in the viola group than that in the placebo group (5 vs. 17, p =0.001). Conclusion: The results of our study showed the safety and efficacy of complementary therapy with Viola odorata L. oil for fever control in febrile neutropenic children during hospital course.
Keywords: skin absorption